Advances in microbial physiology. - Poole, Robert K. (Academic Press, 2004)
First published in 1967, Advances in Microbial Physiology is one of Elsevier's most renowned and acclaimed series. Now edited by Professor Robert Poole, University of Sheffield, Advances in Microbial Physiology continues to publish topical and important reviews, interpreting physiology in its broadest context, to include all material that contributes to our understanding of how microorganisms and their component parts work.